Sirojul Ummah: Music in Social Interaction (Harmonia: Journal of Arts Research and Education, 2020)
This article describes music’s role in social interactions carried out by female members of the Marawis group Sirojul Ummah. The Marawis music is the medium they use in their efforts to convey Islamic knowledge and understanding, both for this group itself and for the surrounding community. The research method used is qualitative, in which data are collected from observations, interviews, and literature review, while the technique in analyzing data is done through a contextual approach. Social interaction in this study is viewed from the associative and dissociative aspects in the form of actions that include rational instrumental action, value rational action, effective action, and traditional action. Music is present in each of these actions. Music is both a subject and an object in social interaction, both in-groups, and out-groups. The associative and dissociative aspects of in-groups can be seen from how musical ideas and performances are developed and honed through practice activities. This activity is carried out because good musical performance is supported by techniques and methods of singing, playing, and presenting musical articulation, ornamentation, and harmonization. At the same time, the associative and dissociative aspects of out-groups can be seen from their activities in filling out events in society. The interaction process is built-in pleasant and informal situations which are shaped by an interest in music and family relationships. Since childhood, they have known each other; thus, they understand the characteristics of each person. Maturity, the maturity of thinking, and acting tend to avoid emotional conflicts that may occur. In this context, music is not only a medium for interaction, but can be a motivation in building these interactions.